Unveiling challenges of maternal health in India’s tribal mothers: Insights from a case series of maternal deaths - Neelam Anupama Toppo; Aditya Thakur; Archana G. Singh; Deepali Soni (Journal of Family Medicine and Primary Care)
Maternal mortality remains a significant public health concern globally, with disparities often evident among marginalized populations, including tribal communities. This case series delves into the complexities surrounding maternal mortality among tribal populations in India, shedding light on the multifaceted factors contributing to this persistent public health issue. Through verbal autopsy and retrospective review of medical records, a series of maternal deaths among tribal mothers were examined. Maternal deaths have been broadly divided into two categories Bottlenecks in quality antenatal services and missed opportunities.